Do ensino intuitivo para a escola ativa: os saberes geométricos nos programas do curso primário paulista, 1890-1950 - Frizzarini, Claudia Regina Boen [UNIFESP] (2014)
This study investigates, in historical perspectives, which changes happened on São Paulo’s primary school teaching programs in the period of 1890 to 1950 in relation to geometry skills. Specifically, it includes subjects, Forms, Geometry, Drawing, Modelling, Arithmetic and Manual work, through annual programs of 1894, 1905, 1918, 1921, 1925, 1934 and 1949/50, analyzing them by its methodology, contents and educational movement. The defined research period was recognizable by two large educational movements: the Modern Pedagogy and the Active School. The sources for this study are the official teaching orientation and the didactic manuals Primeiras Lições de Coisas and Manual do ensino primário. To comprehend the modification on school subjects that occur in the transition of educational movements requires some considerations about scholar culture, appropriations, strategies and tactics, in order to build a historical representation, to produce a history of mathematical education. For this reason, a theoretical-methodological referential is going to be useful as a tool from Cultural History. The source analysis reveals the most significant happenings of the educational movements intuitive and Active school included on geometric subjects, spread over different subjects for different purposes; also this analysis points to new methodologies, contents and subjects that are inserted through the programs that determine how the geometry skills are presented to São Paulo primary school teaching. These continuities and ruptures describe the continuous process, creative and in constant dialogue of official teaching orientation with the ideas and proposals circulating on each historical time, which emphasizes the dynamic character of geometry skills, expressed by changes in school culture.